2009
DOI: 10.1016/j.exppara.2009.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania donovani: Thionins, plant antimicrobial peptides with leishmanicidal activity

Abstract: The leishmanicidal activity of plant antibiotic peptides (PAPs) from the principal families, such wheat thionins, a barley lipid transfer protein and potato defensins and snakins were tested in vitro against Leishmania donovani. Only thionins and defensins were active against this human pathogen at a low micromolar range ofconcentrations, Thionins resulted as the most active peptides tested until now. They collapsed ionic and pH gradients across the parasite plasma membrane together with a rapid depletion of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 12 publications
0
35
0
1
Order By: Relevance
“…We observed that at 300 μg/ml, PvD 1 was able to inhibit 70 % of the protozoan proliferation, after 24 h of incubation (Figure 1). Berrocal-Lobo et al [30] observed the activity of a PTH1 defensin from Solanum tuberosum and a thionin from Triticum aestivum against L. donovani; however, these authors did not test these peptides against L. amazonensis. More recently, Souza et al [29] showed that the natural defensin from Vigna unguiculata seeds (Vu-Def), as well as its recombinant homologues (Vu-Defr), both .…”
Section: Discussionmentioning
confidence: 99%
“…We observed that at 300 μg/ml, PvD 1 was able to inhibit 70 % of the protozoan proliferation, after 24 h of incubation (Figure 1). Berrocal-Lobo et al [30] observed the activity of a PTH1 defensin from Solanum tuberosum and a thionin from Triticum aestivum against L. donovani; however, these authors did not test these peptides against L. amazonensis. More recently, Souza et al [29] showed that the natural defensin from Vigna unguiculata seeds (Vu-Def), as well as its recombinant homologues (Vu-Defr), both .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro thionins are toxic at micromolar concentrations to a wide range of organisms from bacteria and fungi to protozoa and human cells (Fujimura et al 2005;Loeza-Ángeles et al 2008;Berrocal-Lobo et al 2009). Thionins have been found in both seeds and vegetative organs, such as leaves and stems (Stec 2006).…”
Section: Thioninsmentioning
confidence: 99%
“…Other researchers [49] have also discovered new anti-malarial peptides isolated from the non-coding regions of the yeast genome. Berrocal-Lobo et al [7] described in vitro activity of the plant antimicrobial peptides thionins against Leishmania donovani.…”
Section: The Application Of Peptides In Ophthalmologymentioning
confidence: 99%
“…AMPs include all oligoand polypeptides that kill microbes or inhibit their growth, peptides derived from larger proteins, and non-ribosomally synthesized examples [3]. AMPs possess various mechanisms of action, such as permeabilisation of microbial membranes, destabilisation of bilayer lipid structures, formation of micelles or channels within a membrane, lipopolysaccharide (LPS) binding, inhibition of DNA replication and expression of proteins or release of ATP [2,3,4,5,6,7,8,9]. A detailed review of research on peptides can be found in the work of Hancock & Lehrer [4], Zasloff [10], Brodgen et al [11], Mirski et al [12], Kołodziej et al [13], Eckert [14], Brandenburg et al [15], and Devocelle [16].…”
Section: Introductionmentioning
confidence: 99%